2023
DOI: 10.1002/anie.202210651
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned from the Grouping of Chemicals to Assess Risks to Human Health

Abstract: In analogy to the periodic system that groups elements by their similarity in structure and chemical properties, the hazard of chemicals can be assessed in groups having similar structures and similar toxicological properties. Here we review case studies of chemical grouping strategies that supported the assessment of hazard, exposure, and risk to human health. By the EU-REACH and the US-TSCA New Chemicals Program, structural similarity is commonly used as the basis for grouping, but that criterion is not alwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 123 publications
(142 reference statements)
0
13
0
Order By: Relevance
“…The RIFM approach on safety assessments on well over 1000 fragrance substances in peer reviewed literature has shown clear benefit for applying grouping in managing the safe use of substances that are used in consumer products at low levels (< 0.01%). Also well-established principles of grouping utilized in the OECD Toolbox prescribed by ECHA for use by registrants, and the 12 grouping principles as recently published by BASF (Wohlleben et al 2022 ) give a solid basis how scientific grouping can be done.…”
Section: Discussionmentioning
confidence: 99%
“…The RIFM approach on safety assessments on well over 1000 fragrance substances in peer reviewed literature has shown clear benefit for applying grouping in managing the safe use of substances that are used in consumer products at low levels (< 0.01%). Also well-established principles of grouping utilized in the OECD Toolbox prescribed by ECHA for use by registrants, and the 12 grouping principles as recently published by BASF (Wohlleben et al 2022 ) give a solid basis how scientific grouping can be done.…”
Section: Discussionmentioning
confidence: 99%
“…Hierarchical clustering of cannabinoids by their predicted target profiles revealed that some targets were predicted exclusively for certain clusters of cannabinoids (the cannabinoids and their clusters are in Figure 4). Some Wohlleben et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…More extensive in vitro testing could further refine and confirm the cannabinoid clusters. Grouping cannabinoids by target binding profiles may help identify cannabinoids causing similar physiological effects (EFSA Scientific Committee et al, 2021; Organisation for Economic Co‐operation and Development [OECD], 2014; Wohlleben et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure and emission information could serve in the prioritization of chemicals for testing. Utilising exposure information such as mode of exposure (chemicals in food or drinking water) [ 138 , 139 ] or Occupational Exposure Banding strategy for categorization of airborne substances lacking defined limits [ 140 ], could help identify chemicals with high exposure potential. In addition, the hazard level of the toxicity can be used as a criterion, where specific persistent and mobile substances with high toxicity can be targeted for prioritization.…”
Section: Perspectives For Grouping Strategiesmentioning
confidence: 99%
“…The use of in vitro, in vivo, and in silico approaches can aid the grouping and prioritization of chemicals for testing or assessments by regulatory bodies. This can be done by generating grouping hypotheses and justification for inclusion or exclusion criteria for substances in groups [ 140 ]. In particular, novel approaches may generate huge amounts of toxicological and high-throughput “omics” data including metabolomics, transcriptomics, and exposomics to support the validation and establishment of grouping hypotheses needed by regulatory authorities [ 141 ].…”
Section: Perspectives For Grouping Strategiesmentioning
confidence: 99%